Validity and reliability of an objective structured assessment tool for performance of ultrasound-guided regional anaesthesia - Shafqat, Atif; Rafi, M.; Thanawala, Vishal; Bedforth, Nigel M.; Hardman, J.G.; McCahon, Robert A. (Elsevier, 2018)
Background: We aimed to examine the validity and reliability of previously developed criterion-referenced assessment checklist (AC) and global rating scale (GRS) to assess performance in ultrasound-guided regional anaesthesia (UGRA). Methods: Twenty-one anaesthetists’ single, real-time, UGRA procedures (total: 21 blocks) were assessed using 22-item AC and 9-item GRS scored on a 3-point and 5-point Likert scales respectively. We used one-way ANOVA to compare assessment scores between 3 groups (group I: ≤30 blocks in the preceding year; group II: 31–100; group III: >100). Concurrent validity was evaluated using Pearson’s correlation (r). We calculated type-A intra- class correlation coefficient (ICC) using an absolute agreement definition in two-way random effects model, and inter-rater reliability (IRR) using absolute agreement between raters. The inter-item consistency was assessed by Cronbach’s alpha (α). Results: Greater UGRA experience in the preceding year was associated with better AC [F (2,18) 12.01; p <0.001] and GRS [F (2,18) 7.44; p =0.004] scores. There was strong correlation between mean AC and GRS scores [r=0.73 (p <0.001)] and strong inter-item consistency for AC (α = 0.94) and GRS (α = 0.83). The ICC (95% CI) and IRR (95% CI) for AC was 0.96 (0.95 – 0.96) and 0.91 (0.88 – 0.95) respectively and 0.93 (0.90 – 0.94) and 0.80 (0.74 – 0.86) for GRS. Conclusions: Both assessments differentiated between individuals who have performed fewer (≤30) and many (>100) blocks in the preceding year, supporting construct validity. It also established concurrent validity and overall reliability. We recommend both tools may be used in UGRA assessment.